Naturhistorie på 1700-tallet: En global fortelling? - Ochsner, Simone (Academic Quarter | Akademisk kvarter, 2011)
Natural history from the 18th century - a global tale? by Simone Ochsnerdiscusses the apparent paradox that a series of scientific works from the 18th century, which mainly seem to focus on the local, can be considered global tales. Ochsner wonders if it is possible to see natural histories as global tales when they at that time, as regards content, change the focus from the encyclopedic to the regional and local. Ochsner has an etymological starting point, as she asks what global, a concept which has been used for some decades, might have meant in the 18th century.